A green sample preparation method for the determination of bisphenols in honeys - Potortì, Angela Giorgia; Litrenta, Federica; Sgrò, Benedetta; Di Bella, Giuseppa; Albergamo, Ambrogina; Ben Mansour, Hedi; Beltifa, Asma; Benameur, Qada; Lo Turco, Vincenzo (Green Analytical Chemistry, 2023)
•Structural analogues are substituting BPA in production of some consumer products > micro-QuEChERS extraction and the analysis UHPLC-MS/MS was developed and validated > the method was then tested on algerian and tunisian honey samples. Bisphenol A is the most studied compound due to its adverse effects on human health and is one of the most widely used products in contact materials worldwide. However, in recent years, due to stringent restrictions on the use of BPA, structural analogues are substituting BPA in the production of some consumer products. A method based on the Micro-QuEChERS technique and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) was proposed, derived from a previous method based on standard QuEChERS and HPLC-MS/MS. The proposed method was compared with the previous method using the analytical Eco-scale as a verification tool. The results highlight that the proposed method achieved a metric value of 79 points, higher than the required value of 75 points for 'excellent green analysis'. The method was then tested on Algerian and Tunisian honey samples of different floral origins. The results showed that the developed method was satisfactory in terms of recovery, sensitivity, and analysis time, showing good applicability even in a complex matrix such as honey. Low levels of contamination of residues of bisphenol-analogues were found and it can therefore be concluded that the samples analysed do not pose a health risk to consumers with regard to these compounds. [Display omitted]